Use of the Robson classification to assess cesarean section at a medical college hospital in Gujarat, India - Jogia, Ashutosh; Krishna A Mehta (Asian Journal of Medical Sciences, 2022)
Background: The increasing trends for cesarean section (CS) is not only in India but also globally have been a cause of concern. With the aim of comparing and analyzing CS rates worldwide, the WHO suggests Robson’s ten-group classification system (TGCS). Aims and Objectives: To find the group of women with High CS rate. Which will help policymakers to target that specific groups of women for the reduction of overall CS. Materials and Methods: This was a retrospective study design using hospital records for women delivered between December 1, 2020, and November 30, 2021. Data were entered and analyzed using Excel 2019 and presented in percentages after using Robson’s TGCS. Results: Out of total 5514 women delivered during the study period, 2262 (41.02%) were delivered by CS. Group 1 and Group 2 included a total of 41.49% of women in the present study. The high CS rates were in Group 9 (abnormal lie) – 100%, Group 5 (previous CS) – 97.35%, and Group 6 (breech, nulliparous) – 77.47%. In all CS, the maximum contribution was done by Group 5 (37.36%) and Group 2 (28.47%). Conclusions: The result indicates that Group 5 women with previous CS and Group 2 women with induced labor contributed the maximum to overall CS rates. Trial of labor after CS should be used as a routine. The specific guideline should be followed about the time and cause for induction of labor to decrease the CS rate that occurs due to failed inductions. To monitor CS rate and take actions accordingly, Robson’s TGCS should be used in all health facilities where delivery is done.